Uma tradução comentada da epistolografia de Virginia Woolf e Lytton Strachey - Carvalho, Geórgia Gardênia Brito Cavalcante (2017)
This research has as main objective a commented translation to Brazilian Portuguese of a selection of letters in English language, exchanged between Virginia Woolf and Lytton Strachey during the years of 1906 to 1912, before the consolidation of Woolf as referential writer for the literature produced in the 20th century. The difficulties generated by the diachronic distance of almost one hundred years, due to the difference between the structures of source language and target language, as well as the British and Brazilian cultural idiosyncrasies acted as a leitmotiv to support this work. The commented translation I developed it took into account the cultural and linguistic aspects of the source text, with emphasis on both writers' reading impressions about a certain number of literary works and their respective authors. I proposed as secondary objectives of this research, the possibility of contributing to epistemological studies in the field of translation studies, thus generating translated material unpublished in Brazilian Portuguese, in addition to contribute to the vast critical fortune of Woolf and Strachey. It is also part of this work a discussion about the epistolary practice and its peculiarities from the process of translation of the missives. The theoretical precepts of this research are based on the studies of Berman (2002, 2013), Levý (2000), Rónai (1981) and Lefevere (1992), among others.